1966
DOI: 10.1051/apido:19660402
|View full text |Cite
|
Sign up to set email alerts
|

Les Modalités De l'ADAPTATION Des Abeilles (Apis Mellifica L.) Au Milieu Naturel

Abstract: L'auteur après avoir décrit les conditions bioclimatiques propres à trois milieux différents (Région Parisienne, Grande Lande de Gascogne, environs d'Avignon) expose les résultats d'expériences de permutation de colonies d'abeilles de la même race géographique (Apis !nellifica mellifica) mais originaires de deux des milieux décrits. :lprès leur déplacement les colonies conservent des traits de comportement adaptés au milieu antérieur. L'auteur discute de l'origine et de l'importance du phénomène en matière de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 0 publications
5
32
0
2
Order By: Relevance
“…Our findings are similar to research of Louveaux et al (1966), who transposed bees originating in areas with a spring or summer peak, and demonstrated that the bees were unadapted to the new environment, which was shown by worse performances (weight of hive, pollen harvest, extent of the brood-comb) than those of the indigenous colonies. They found that change of the queen had the same effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are similar to research of Louveaux et al (1966), who transposed bees originating in areas with a spring or summer peak, and demonstrated that the bees were unadapted to the new environment, which was shown by worse performances (weight of hive, pollen harvest, extent of the brood-comb) than those of the indigenous colonies. They found that change of the queen had the same effect.…”
Section: Discussionsupporting
confidence: 90%
“…However, pollen is collected on the basis of colony needs, with small quantities kept as a reserve (Dreller et al, 1999). In our experiment, the local genotype had higher pollen reserve in most measurements, which is similar to findings of Louveaux et al (1966).…”
Section: Discussionsupporting
confidence: 86%
“…In France one of the country's four identified ecotypes of A. m. mellifera occurs in the Landes region (Louveaux et al, 1966), characterized by an unusual brood cycle adapted to the late season blooming of ling heather, Calluna vulgaris. This brood cycle was found in almost 50% of the colonies analyzed by Strange et al (2007) and, therefore, several morphological and molecular approaches have been used to distinguish this ecotype from introduced Buckfast hybrids (Strange et al, 2008).…”
Section: Present Conservation Programsmentioning
confidence: 99%
“…On a constaté, grâce à ce type de recherches que des populations locales d'abeilles se forment et qu'elles présentent une nette adaptation au milieu. Ainsi, alors que dans le bassin parisien le cycle biologique annuel des colonies d'abeilles ne présente qu'un seul sommet en fin du mois de juin, celui des abeilles des Landes est à deux sommets, bien adapté à la floraison estivale de la callune (Louveaux et al, 1966).…”
Section: La Recolte Du Pollen Par Les Abeilles Domestiquesunclassified